Effect of simultaneously introduced bulky pendent group and amide unit on optical transparency and dimensional stability of polyimide film. (15th June 2022) - Zuo, Hongtao; Chen, Yuting; Qian, Guangtao; Yao, Fen; Li, Haibei; Dong, Jie; Zhao, Xin; Zhang, Qinghua
Graphical abstract: A novel highly transparent polyimide film with reduced CTE value was synthesized by introducing bulky pendent group and amide unit and the effects of designed structures on the optical transparency and dimensional stability of polyimide film were studied in detail. Highlights: Several PI films were fabricated by introducing bulky pendent group and amide unit. The effects of introduced groups on the properties of PI films were studied. The film possesses good optical properties with λcutoff of 384 nm and T450 nm of 81%. The film with designed structure displays reduced CTE value of 45 ppm/℃. Abstract: Monomers of 4, 4′-((4-(trifluoromethyl)phenyl)methylene)bis(2, 6-dimethylaniline) (3FTMDT) and N, N'-(2, 2′-bis(trifluoromethyl)-[1, 1′-biphenyl]-4, 4′-diyl)bis(1, 3-dioxo-1, 3-dihydroisobenzofuran-5-carboxamide) (TA-TFMB) were synthesized and designed to fabricate polyimide film with simultaneously designed bulky pendent group and amide unit in polymer chains and their effects on the optical transparency and dimensional stability of films were investigated in detail. The prepared polyimide (3FTMDT/TA-TFMB) film possesses highly optical transparency (λcutoff  = 384 nm, T450 nm  = 81%, Haze = 0.86) and lighter color ( L *=95.09, a *=-2.14, b *=6.44) with the in-plane coefficient of linear thermal expansion of 45 ppm/ o C. Meanwhile, the film presents good thermal stability and mechanical properties, with a glass transition temperature ( Tg ) of 337 °C and 5 wt% decomposition temperature of 459 °C under N2, the fracture strength and tensile modulus of the film are 105 MPa and 2.2 GPa, respectively. The film also exhibits low dielectric performances with intrinsic dielectric constant of 2.29 and dielectric loss of 8 × 10 -3 at 10 KHz, and which could keep stable up to 280 °C. In addition, the film shows good solubility in common solvents and is easy to be processed. The highly transparent polyimide film with reduced coefficient of linear thermal expansion is expected to be used as substrate material for flexible display or other photoelectric fields.